The socio-economic impact of al-hayat relief foundation on muslims in Abeokuta, Nigeria (2015)
Due to the nature of large financial institutions which target high- scale and complex financial transactions capable of yielding high returns, the masses are usually excluded from financial services necessitating the intervention of the informal sector, cooperatives inclusive. Moreover, the prohibition of riba (interest) by Islam has brought about the establishment of a number of interest-free Islamic cooperative societies one of which is al-Hayat Relief Foundation. Previous studies have focused on principles, practices and empowerment potentials of cooperative societies, however, none of these studies within our reach seems to have provided detailed explanation on the success or otherwise of most of the socio-economic strategies adopted by al-Hayat Relief Foundation in Abeokuta. Hence, this study aims at examining the impact of Al- Hayat Relief Foundation in enhancing the welfare and empowerment of members, and boosting their financial standing. The study investigated the possible hitches being encountered in its operations with a view to suggesting ways of improving its services. Data were sourced through key-informant interviews and the administering of questionnaires to members of the Foundation across the four branches in Abeokuta: Onikolobo, Lantoro, Kuto and Asero, while descriptive statistics was used in analysing them. Whereas the Foundation has improved the socio-economic standing of its members, there is the need to do more for the benefits to circulate among members. The concept of Islamic business ethics also needs to be properly applied by the cooperative.